PROAMPHIBOS (BOVINI, BOVIDAE, MAMMALIA) FROM THE TATROT FORMATION IN THE UPPER SIWALIKS OF PAKISTAN - M. A. Khan; M. Iqbal; A. Ghaffar; M. Akhtar (Journal of Animal and Plant Sciences, 2009)
Proamphibos was a bovine present only in the fresh water deposits of the Upper Siwaliks and its tertiary fossil record is poorly known. New fossil remains of the Bovini genus Proamphibos are described. It includes a maxillary ramus bearing P3-M3. The analysis of the dental characters was allowed individual variations and contributes knowledge about the primitive bovine.
Keywords: Proamphibos; Bovine; Tatrot Formation; Upper Siwaliks; Pliocene.